An Analysis of the Effectiveness of Training Sociodynamic Counseling in Improving the Communication Skills of the Librarians of Khomeini Shahr\'s Public Libraries - Marzieyh Malekiha; Zahra Shahgholi (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2020)
Purpose: According to Scharf (2013), the library profession is one of the professions in which communication plays an important role. In other words, not only the quantity and quality of library equipment are effective in attracting the client to the library, but also the quality of the librarian's communication is important. With the evolution of approaches and theories in the field of counseling and psychotherapy as a communication-oriented profession, various interventions have emerged to improve the quality of communication. The Sociodynamic approach is one of these interventions, which was put forward by R. Vance Peavy in 2004. Method: This research is a quasi-experimental study using a pretest-posttest design on an experimental group and a control group. The research population included all public libraries' librarians of Khomeyni Shahr County in 2019, from whom 30 members were selected by using the convenience sampling technique and were randomly divided to an experimental group and a control group (each group with 15 member). To assess the librarians' communication skills, the Queendom Interpersonal Communication Skills questionnaire (2004) was used. This questionnaire has 34 questions that have been developed to measure the adult communication skills. The reliability of this questionnaire in Hossein Chari & Sacrifice's research (2005) is equal to 0.69 and in Yousefi & Khaiier's research (2002) is equal to 0.77 and in Mahmoudi and Najafi's research (2012) is reported to be 0.81. To analyze the data, the SPSS-23 statistical software and the indicators of descriptive statistics (median and standard deviation) and inferential statistics (i.e. analysis of Covariance) were used. Findings: The results show a meaningful difference between the mean scores of relationship skills and their dimensions in the experimental and control groups. Accordingly, it can be concluded that training sociodynamic approach has been effective in the enhancement of communication skills and their dimensions (ability to receive & send massage, emotional control, listening, insight into the process of communication and communication with decisiveness) among the librarians. Originality/value: By reviewing the studies carried out thus far in the field of librarian scope, one can realize the importance of the variable of communication in this profession. However, most of the studies conducted in this regard have been descriptive and there is no study which has examined the effectiveness of an intervention in improving the quality of Librarians' communication skills. Therefore, this study is valuable in terms of method and subject.